2023
DOI: 10.3389/fneur.2023.1156879
|View full text |Cite
|
Sign up to set email alerts
|

Trimethylamine-N-oxide: a potential biomarker and therapeutic target in ischemic stroke

Abstract: Ischemic stroke is by far the most common cerebrovascular disease and a major burden to the global economy and public health. Trimethylamine-N-oxide (TMAO), a small molecule compound produced by the metabolism of intestinal microorganisms, is reportedly associated with the risk of stroke, as well as the severity and prognosis of stroke; however, this conclusion remains contentious. This article reviews the production of TMAO, TMAO’s relationship with different etiological types of ischemic stroke, and the poss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 70 publications
0
2
0
Order By: Relevance
“…In contrast to circulating choline, we did not find an association between plasma TMAO levels and CVD risk or mortality in our population‐based cohorts. Even though a number of studies have shown a relationship between TMAO levels and CVD risk, these results are mostly derived from individuals with a high risk of CVD, existing disease, or multimorbidity [ 6 , 7 , 8 , 43 , 44 , 45 , 46 ]. In line with our results, a few population‐based studies did not identify an association between TMAO and cardiometabolic markers, carotid intima media thickness, CVD events including heart attack and stroke and mortality, either [ 9 , 21 , 47 , 48 ], while some other studies did report significant associations [ 10 , 11 , 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to circulating choline, we did not find an association between plasma TMAO levels and CVD risk or mortality in our population‐based cohorts. Even though a number of studies have shown a relationship between TMAO levels and CVD risk, these results are mostly derived from individuals with a high risk of CVD, existing disease, or multimorbidity [ 6 , 7 , 8 , 43 , 44 , 45 , 46 ]. In line with our results, a few population‐based studies did not identify an association between TMAO and cardiometabolic markers, carotid intima media thickness, CVD events including heart attack and stroke and mortality, either [ 9 , 21 , 47 , 48 ], while some other studies did report significant associations [ 10 , 11 , 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…The gut microbiota and its metabolites may affect the risk factors of stroke, such as hypertension, obesity, and diabetes, or signal inflammation and immune responses during atherosclerosis and thrombosis . To be specific, a growing body of evidence suggests that Trimethylamine-N-oxide (TMAO), a small molecular compound derived from the metabolism of intestinal microorganisms, is associated with the elevated risk of stroke, as well as the severity and prognosis of stroke (Liu et al, 2023). Clinical evidence from dose-response meta-analyses also show the circulating TMAO is positively associated with an increased probability of risk factors in stroke, such as hypertension (Abbasalizad Farhangi and Vajdi, 2021), and inflammatory parameters involved in the pathological process of atherosclerosis, such as C-reactive protein (Farhangi and Vajdi, 2020).…”
Section: Introductionmentioning
confidence: 99%